Melanoma and immunotherapy bridge 2015. Issue 1 (July 2016) - Nanda, Vashisht; Peng, Weiyi; Hwu, Patrick; Davies, Michael; Ciliberto, Gennaro; Fattore, Luigi; Malpicci, Debora; Aurisicchio, Luigi; Ascierto, Paolo; Croce, Carlo; Mancini, Rita; Spranger, Stefani; et al.
Table of contents MELANOMA BRIDGE 2015 KEYNOTE SPEAKER PRESENTATIONS Molecular and immuno-advances K1 Immunologic and metabolic consequences of PI3K/AKT/mTOR activation in melanoma Vashisht G. Y. Nanda, Weiyi Peng, Patrick Hwu, Michael A. Davies K2 Non-mutational adaptive changes in melanoma cells exposed to BRAF and MEK inhibitors help the establishment of drug resistance Gennaro Ciliberto, Luigi Fattore, Debora Malpicci, Luigi Aurisicchio, Paolo Antonio Ascierto, Carlo M. Croce, Rita Mancini K3 Tumor-intrinsic beta-catenin signaling mediates tumor-immune avoidance Stefani Spranger, Thomas F. Gajewski K4 Intracellular tumor antigens as a source of targets of antibody-based immunotherapy of melanoma Yangyang Wang, Soldano Ferrone Combination therapies K5 Harnessing radiotherapy to improve responses to immunotherapy in cancer Claire Vanpouille-Box, Erik Wennerberg, Karsten A. Pilones, Silvia C. Formenti, Sandra Demaria K6 Creating a T cell-inflamed tumor microenvironment overcomes resistance to checkpoint blockade Haidong Tang, Yang Wang, Yang-Xin Fu K7 Biomarkers for treatment decisions? Reinhard Dummer K8 Combining oncolytic therapies in the era of checkpoint inhibitors Igor Puzanov K9 Immune checkpoint blockade for melanoma: should we combine or sequence ipilimumab and PD-1 antibody therapy? Michael A. Postow News in immunotherapy K10 An update on adjuvant and neoadjuvant therapy for melanom Ahmad Tarhini K11 Targeting multiple inhibitory receptors in melanoma Joe-Marc Chauvin, Ornella Pagliano, Julien Fourcade, Zhaojun Sun, Hong Wang, Cindy Sanders, John M. Kirkwood, Tseng-hui Timothy Chen, Mark Maurer, Alan J. Korman, Hassane M. Zarour K12 Improving adoptive immune therapy using genetically engineered T cells David F. Stroncek Tumor microenvironment and biomarkers K13 Myeloid cells and tumor exosomes: a crosstalk for assessing immunosuppression? Veronica Huber, Licia Rivoltini K14 Update on the SITC biomarker taskforce: progress and challenges Magdalena Thurin World-wide immunoscore task force: an update K15 The immunoscore in colorectal cancer highlights the importance of digital scoring systems in surgical pathology Tilman Rau, Alessandro Lugli K16 The immunoscore: toward an integrated immunomonitoring from the diagnosis to the follow up of cancer's patients Franck Pagès Economic sustainability of melanoma treatments: regulatory, health technology assessment and market access issues K17 Nivolumab, the regulatory experience in immunotherapy Jorge Camarero, Arantxa Sancho K18 Evidence to optimize access for immunotherapies Claudio Jommi ORAL PRESENTATIONS Molecular and immuno-advances O1 Ipilimumab treatment results in CD4 T cell activation that is concomitant with a reduction in Tregs and MDSCs Yago Pico de Coaña, Maria Wolodarski, Yuya Yoshimoto, Giusy Gentilcore, Isabel Poschke, Giuseppe V. Masucci, Johan Hansson, Rolf Kiessling O2 Evaluation of prognostic and therapeutic potential of COX-2 and PD-L1 in primary and metastatic melanoma Giosuè Scognamiglio, Francesco Sabbatino, Federica Zito Marino, Anna Maria Anniciello, Monica Cantile, Margherita Cerrone, Stefania Scala, Crescenzo D'alterio, Angela Ianaro, Giuseppe Cirino, Paolo Antonio Ascierto, Giuseppina Liguori, Gerardo Botti O3 Vemurafenib in patients with BRAFV600 mutation–positive metastatic melanoma: final overall survival results of the BRIM-3 study Paul B. Chapman, Caroline Robert, James Larkin, John B. Haanen, Antoni Ribas, David Hogg, Omid Hamid, Paolo Antonio Ascierto, Alessandro Testori, Paul Lorigan, Reinhard Dummer, Jeffrey A. Sosman, Keith T. Flaherty, Huibin Yue, Shelley Coleman, Ivor Caro, Axel Hauschild, Grant A. McArthur O4 Updated survival, response and safety data in a phase 1 dose-finding study (CA209-004) of concurrent nivolumab (NIVO) and ipilimumab (IPI) in advanced melanoma Mario Sznol, Margaret K. Callahan, Harriet Kluger, Michael A. Postow, RuthAnn Gordan, Neil H. Segal, Naiyer A. Rizvi, Alexander Lesokhin, Michael B. Atkins, John M. Kirkwood, Matthew M. Burke, Amanda Ralabate, Angel Rivera, Stephanie A. Kronenberg, Blessing Agunwamba, Mary Ruisi, Christine Horak, Joel Jiang, Jedd Wolchok Combination therapies O5 Efficacy and correlative biomarker analysis of the coBRIM study comparing cobimetinib (COBI) + vemurafenib (VEM) vs placebo (PBO) + VEM in advanced BRAF-mutated melanoma patients (pts) Paolo A. Ascierto, Grant A. McArthur, James Larkin, Gabriella Liszkay, Michele Maio, Mario Mandalà, Lev Demidov, Daniil Stoyakovskiy, Luc Thomas, Luis de la Cruz-Merino, Victoria Atkinson, Caroline Dutriaux, Claus Garbe, Matthew Wongchenko, Ilsung Chang, Daniel O. Koralek, Isabelle Rooney, Yibing Yan, Antoni Ribas, Brigitte Dréno O6 Preliminary clinical safety, tolerability and activity results from a Phase Ib study of atezolizumab (anti-PDL1) combined with vemurafenib in BRAFV600-mutant metastatic melanoma Ryan Sullivan, Omid Hamid, Manish Patel, Stephen Hodi, Rodabe Amaria, Peter Boasberg, Jeffrey Wallin, Xian He, Edward Cha, Nicole Richie, Marcus Ballinger, Patrick Hwu O7 Preliminary safety and efficacy data from a phase 1/2 study of epacadostat (INCB024360) in combination with pembrolizumab in patients with advanced/metastatic melanoma Thomas F. Gajewski, Omid Hamid, David C. Smith, Todd M. Bauer, Jeffrey S. Wasser, Jason J. Luke, Ani S. Balmanoukian, David R. Kaufman, Yufan Zhao, Janet Maleski, Lance Leopold, Tara C. Gangadhar O8 Primary analysis of MASTERKEY-265 phase 1b study of talimogene laherparepvec (T-VEC) and pembrolizumab (pembro) for unresectable stage IIIB-IV melanoma Reinhard Dummer, Georgina V. Long, Antoni Ribas, Igor Puzanov, Olivier Michielin, Ari VanderWalde, Robert H.I. Andtbacka, Jonathan Cebon, Eugenio Fernandez, Josep Malvehy, Anthony J. Olszanski, Thomas F. Gajewski, John M. Kirkwood, Christine Gause, Lisa Chen, David R. Kaufman, Jeffrey Chou, F. Stephen Hodi News in immunotherapy O9 Two-year survival and safety update in patients (pts) with treatment-naïve advanced melanoma (MEL) receiving nivolumab (NIVO) or dacarbazine (DTIC) in CheckMate 066 Victoria Atkinson, Paolo A. Ascierto, Georgina V. Long, Benjamin Brady, Caroline Dutriaux, Michele Maio, Laurent Mortier, Jessica C. Hassel, Piotr Rutkowski, Catriona McNeil, Ewa Kalinka-Warzocha, Celeste Lebbé, Lars Ny, Matias Chacon, Paola Queirolo, Carmen Loquai, Parneet Cheema, Alfonso Berrocal, Karmele Mujika Eizmendi, Luis De La Cruz-Merino, Gil Bar-Sela, Christine Horak, Joel Jiang, Helene Hardy, Caroline Robert O10 Efficacy and safety of nivolumab (NIVO) in patients (pts) with advanced melanoma (MEL) who were treated beyond progression in CheckMate 066/067 Georgina V. Long, Jeffrey S. Weber, James Larkin, Victoria Atkinson, Jean-Jacques Grob, Reinhard Dummer, Caroline Robert, Ivan Marquez-Rodas, Catriona McNeil, Henrik Schmidt, Karen Briscoe, Jean-François Baurain, F. Stephen Hodi, Jedd D. Wolchok Tumor microenvironment and biomarkers O11 New biomarkers for response/resistance to BRAF inhibitor therapy in metastatic melanoma Rosamaria Pinto, Simona De Summa, Vito Michele Garrisi, Sabino Strippoli, Amalia Azzariti, Gabriella Guida, Michele Guida, Stefania Tommasi O12 Chemokine receptor patterns in lymphocytes mirror metastatic spreading in melanoma and response to ipilimumab Nicolas Jacquelot, David Enot, Caroline Flament, Jonathan M. Pitt, Nadège Vimond, Carolin Blattner, Takahiro Yamazaki, Maria-Paula Roberti, Marie Vetizou, Romain Daillere, Vichnou Poirier-Colame, Michaëla Semeraro, Anne Caignard, Craig L Slingluff Jr, Federica Sallusto, Sylvie Rusakiewicz, Benjamin Weide, Aurélien Marabelle, Holbrook Kohrt, Stéphane Dalle, Andréa Cavalcanti, Guido Kroemer, Anna Maria Di Giacomo, Michaele Maio, Phillip Wong, Jianda Yuan, Jedd Wolchok, Viktor Umansky, Alexander Eggermont, Laurence Zitvogel O13 Serum levels of PD1- and CD28-positive exosomes before Ipilimumab correlate with therapeutic response in metastatic melanoma patients Passarelli Anna, Tucci Marco, Stucci Stefania, Mannavola Francesco, Capone Mariaelena, Madonna Gabriele, Ascierto Paolo Antonio, Silvestris Franco O14 Immunological prognostic factors in stage III melanomas María Paula Roberti, Nicolas Jacquelot, David P Enot, Sylvie Rusakiewicz, Michaela Semeraro, Sarah Jégou, Camila Flores, Lieping Chen, Byoung S. Kwon, Ana Carrizossa Anderson, Caroline Robert, Christophe Borg, Benjamin Weide, François Aubin, Stéphane Dalle, Michele Maio, Jedd D. Wolchok, Holbrook Kohrt, Maha Ayyoub, Guido Kroemer, Aurélien Marabelle, Andréa Cavalcanti, Alexander Eggermont, Laurence Zitvogel POSTER PRESENTATIONS Molecular and immuno-advances P1 Human melanoma cells resistant to B-RAF and MEK inhibition exhibit mesenchymal-like features Anna Lisa De Presbiteris, Fabiola Gilda Cordaro, Rosa Camerlingo, Federica Fratangelo, Nicola Mozzillo, Giuseppe Pirozzi, Eduardo J. Patriarca, Paolo A. Ascierto, Emilia Caputo P2 Anti-proliferative and pro-apoptotic effect of ABT888 on melanoma cell lines and its potential role in the treatment of melanoma resistant to B-RAF inhibitors Federica Fratangelo, Rosa Camerlingo, Emilia Caputo, Maria Letizia Motti, Rosaria Falcone, Roberta Miceli, Mariaelena Capone, Gabriele Madonna, Domenico Mallardo, Maria Vincenza Carriero, Giuseppe Pirozzi and Paolo Antonio Ascierto P3 Involvement of the L-cysteine/CSE/H2S pathway in human melanoma progression Elisabetta Panza, Paola De Cicco, Chiara Armogida, Giuseppe Ercolano, Rosa Camerlingo, Giuseppe Pirozzi, Giosuè Scognamiglio, Gerardo Botti, Giuseppe Cirino, Angela Ianaro P4 Cancer stem cell antigen revealing pattern of antibody variable region genes were defined by immunoglobulin repertoire analysis in patients with malignant melanoma Beatrix Kotlan, Gabriella Liszkay, Miri Blank, Timea Balatoni, Judit Olasz, Emil Farkas, Andras Szollar, Akos Savolt, Maria Godeny, Orsolya Csuka, Szabolcs Horvath, Klara Eles, Yehuda Shoenfeld and Miklos Kasler P5 Upregulation of Neuregulin-1 expression is a hallmark of adaptive response to BRAF/MEK inhibitors in melanoma Debora Malpicci, Luigi Fattore, Susan Costantini, Francesca Capone, Paolo Antonio Ascierto, Rita Mancini, Gennaro Ciliberto P6 HuR positively regulates migration of HTB63 melanoma cells Farnaz Moradi, Pontus Berglund, Karin Leandersson, Rickard Linnskog, Tommy Andersson, Chandra Prakash Prasad P7 Prolyl 4- (C-P4H) hydroxylases have opposing effects in malignant melanoma: implication in prognosis and therapy Cristiana Lo Nigro, Laura Lattanzio, Hexiao Wang, Charlotte Proby, Nelofer Syed, Marcella Occelli, Carolina Cauchi, Marco Merlano, Catherine Harwood, Alastair Thompson, Tim Crook P8 Urokinase receptor antagonists: novel agents for the treatment of melanoma Maria Letizia Motti, Katia Bifulco, Vincenzo Ingangi, Michele Minopoli, Concetta Ragone, Federica Fratangelo, Antonello Pessi, Gennaro Ciliberto, Paolo Antonio Ascierto, Maria Vincenza Carriero P9 Exosomes released by melanoma cell lines enhance chemotaxis of primary tumor cells Francesco Mannavola, Stella D'Oronzo, Claudia Felici, Marco Tucci, Antonio Doronzo, Franco Silvestris P10 New insights in mitochondrial metabolic reprogramming in melanoma Anna Ferretta, Gabriella Guida, Stefania Guida, Imma Maida, Tiziana Cocco, Sabino Strippoli, Stefania Tommasi, Amalia Azzariti, Michele Guida P11 Lenalidomide restrains the proliferation in melanoma cells through a negative regulation of their cell cycle Stella D'Oronzo, Anna Passarelli, Claudia Felici, Marco Tucci, Davide Quaresmini, Franco Silvestris Combination therapies P12 Chemoimmunotherapy elicits polyfunctional anti-tumor CD8 + T cells depending on the activation of an AKT pathway sustained by ICOS Ornella Franzese, Belinda Palermo, Cosmo Di Donna, Isabella Sperduti, MariaLaura Foddai, Helena Stabile, Angela Gismondi, Angela Santoni, Paola Nisticò P13 Favourable toxicity profile of combined BRAF and MEK inhibitors in metastatic melanoma patients Andrea P. Sponghini, Francesca Platini, Elena Marra, David Rondonotti, Oscar Alabiso, Maria T. Fierro, Paola Savoia, Florian Stratica, Pietro Quaglino P14 Electrothermal bipolar vessel sealing system dissection reduces seroma output or time to drain removal following axillary and ilio-inguinal node dissection in melanoma patients: a pilot study Di Monta Gianluca, Caracò Corrado, Di Marzo Massimiliano, Marone Ugo, Di Cecilia Maria Luisa, Mozzillo Nicola News in immunotherapy P15 Clinical and immunological response to ipilimumab in a metastatic melanoma patient with HIV infection Francesco Sabbatino, Celeste Fusciello1, Antonio Marra, Rosario Guarrasi, Carlo Baldi, Rosa Russo, Di Giulio Giovanni, Vincenzo Faiola, Pio Zeppa, Stefano Pepe P16 Immunotherapy and hypophysitis: a case report Elisabetta Gambale, Consiglia Carella, Alessandra Di Paolo, Michele De Tursi Tumor microenvironment and biomarkers P17 New immuno- histochemical markers for the differential diagnosis of atypical melanocytic lesions with uncertain malignant potential Laura Marra, Giosuè Scognamiglio, Monica Cantile, Margherita Cerrone, Fara De Murtas, Valeria Sorrentino, Anna Maria Anniciello, Gerardo Botti P18 Utility of simultaneous measurement of three serum tumor markers in melanoma patients Angela Sandru, Silviu Voinea, Eugenia Panaitescu, Madalina Bolovan, Adina Stanciu, Sabin Cinca P19 The significance of various cut-off levels of melanoma inhibitory activity in evaluation of cutaneous melanoma patients Angela Sandru, Silviu Voinea, Eugenia Panaitescu, Madalina Bolovan, Adina Stanciu, Sabin Cinca P20 The long noncoding RNA HOTAIR is associated to metastatic progression of melanoma and it can be identified in the blood of patients with advanced disease Chiara Botti, Giosuè Scognamiglio, Laura Marra, Gabriella Aquino, Rosaria Falcone, Annamaria Anniciello, Paolo Antonio Ascierto, Gerardo Botti, Monica Cantile Other P21 The effect of Sentinel Lymph Node Biopsy in melanoma mortality: timing of dissection Cristina Fortes, Simona Mastroeni, Alessio Caggiati, Francesca Passarelli, Alba Zappalà, Maria Capuano, Riccardo Bono, Maurizio Nudo, Claudia Marino, Paola Michelozzi P22 Epidemiological survey on related psychopathology in melanoma Valeria De Biasio, Vincenzo C. Battarra IMMUNOTHERAPY BRIDGE KEYNOTE SPEAKER PRESENTATIONS Immunotherapy beyond melanoma K19 Predictor of response to radiation and immunotherapy Silvia Formenti K20 Response and resistance to PD-1 pathway blockade: clues from the tumor microenvironment Maria Libera Ascierto, Tracee L. McMiller, Alan E. Berger, Ludmila Danilova, Robert A. Anders, George J. Netto, Haiying Xu, Theresa S. Pritchard, Jinshui Fan, Chris Cheadle, Leslie Cope, Charles G. Drake, Drew M. Pardoll, Janis M. Taube and Suzanne L. Topalian K21 Combination immunotherapy with autologous stem cell transplantation, protein immunization, and PBMC reinfusion in myeloma patients Sacha Gnjatic, Sarah Nataraj, Naoko Imai, Adeeb Rahman, Achim A. Jungbluth, Linda Pan, Ralph Venhaus, Andrew Park, Frédéric F. Lehmann, Nikoletta Lendvai, Adam D. Cohen, and Hearn J. Cho K22 Anti-cancer immunity despite T cell "exhaustion" Speiser Daniel Immunotherapy in oncology (I-O): data from clinical trial K23 The Checkpoint Inhibitors for the Treatment of Metastatic Non-small Cell Lung Cancer (NSCLC) Vera Hirsh